2017
DOI: 10.1039/c7ee02307c
|View full text |Cite
|
Sign up to set email alerts
|

Towards identifying the active sites on RuO2(110) in catalyzing oxygen evolution

Abstract: Surface structural transitions and active sites are identified using X-ray scattering and density functional theory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
363
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 344 publications
(390 citation statements)
references
References 77 publications
23
363
4
Order By: Relevance
“…Intriguingly, higher oxidized surface terminations with adsorbed hydroperoxo (OOH) or superoxo (OO) groups are very unfavorable at the nanosheet surface, cf. However, higher oxidized structures such as *O/*O and *OOH/*O quickly gain stability with increasing potential and start to become most stable at potentials around U ≈1.5 V. As expected from the lower coordination of the edge sites, this is now much more similar to results obtained for the rutile (110) surface by Rao et al [29] Nevertheless, highly oxidized edge terminations like fully covered hydroperoxo (*OOH/*OOH) and superoxo (*OO/*OO) are still unfavorable (see blue lines in Figure 5a,b), clearly distinguishing the nanosheet edge from the low-index rutile surfaces. This is in strong contrast to the situation at rutile RuO 2 surfaces, where such higher oxidation intermediates at the surface are much more stable and correspondingly dominate the resting state of the surface even in the OER regime.…”
Section: Theoretical Analysis and Mechanismsupporting
confidence: 85%
See 3 more Smart Citations
“…Intriguingly, higher oxidized surface terminations with adsorbed hydroperoxo (OOH) or superoxo (OO) groups are very unfavorable at the nanosheet surface, cf. However, higher oxidized structures such as *O/*O and *OOH/*O quickly gain stability with increasing potential and start to become most stable at potentials around U ≈1.5 V. As expected from the lower coordination of the edge sites, this is now much more similar to results obtained for the rutile (110) surface by Rao et al [29] Nevertheless, highly oxidized edge terminations like fully covered hydroperoxo (*OOH/*OOH) and superoxo (*OO/*OO) are still unfavorable (see blue lines in Figure 5a,b), clearly distinguishing the nanosheet edge from the low-index rutile surfaces. This is in strong contrast to the situation at rutile RuO 2 surfaces, where such higher oxidation intermediates at the surface are much more stable and correspondingly dominate the resting state of the surface even in the OER regime.…”
Section: Theoretical Analysis and Mechanismsupporting
confidence: 85%
“…A symmetric two-nanosheet model (Figure 5c) and four O 3f atoms at the inner face between the sheets, which allows assessing H coverages in 25% steps at both O 3f types. [29] We attribute this qualitative difference to the different crystallographic structure of the nanosheet surface and the low-index facets of rutile, in particular to the much studied (110) facet. The determined relative stabilities of the energetically most preferable terminations are plotted in Figure 5a.…”
Section: Theoretical Analysis and Mechanismmentioning
confidence: 98%
See 2 more Smart Citations
“…It is beneficial for transporting carriers which endow rutile with excellent oxygen-related catalytic activity, as shown in Tables 1 and 2. [62] For RuO 2 , its OER activities keep increase followed by (101), (001), and (111) facet. Recently, Yang et al found that (100) surface of IrO 2 and RuO 2 showed a more active in alkaline environments than the most thermodynamically stable (110) surface.…”
Section: Rutiles and Their Hollow Structuresmentioning
confidence: 97%